Inflammation-Associated Synaptic Alterations as Shared Threads in Depression and Multiple Sclerosis - Bruno, Antonio; Dolcetti, Ettore; Rizzo, Francesca Romana; Fresegna, Diego; Musella, Alessandra; Gentile, Antonietta; De Vito, Francesca; Caioli, Silvia; Guadalupi, Livia; Bullitta, Silvia; Vanni, Valentina; Balletta, Sara; et al. (Frontiers in Cellular Neuroscience, 2020)
In the past years, several theories have been advanced to explain the pathogenesis of Major Depressive Disorder (MDD), a neuropsychiatric disease that causes disability in general population. Several theories have been proposed to define the MDD pathophysiology such as the classic “monoamine-theory” or the “glutamate hypothesis”. All these theories have been recently integrated by evidence highlighting inflammation as a pivotal player in developing depressive symptoms. Proinflammatory cytokines have been indeed claimed to contribute to stress-induced mood disturbances and to major depression, indicating a widespread role of classical mediators of inflammation in emotional control. Moreover, during systemic inflammatory diseases, peripherally released cytokines circulate in the blood, reach the brain and cause anxiety, anhedonia, social withdrawal, fatigue, and sleep disturbances. Accordingly, chronic inflammatory disorders, such as the inflammatory autoimmune disease multiple sclerosis (MS), have been associated to higher risk of MDD, in comparison with overall population. Importantly, in both MS patients and in its experimental mouse model Experimental Autoimmune Encephalomyelitis (EAE), the notion that depressive symptoms are reactive epiphenomenon to the MS pathology has been recently challenged by the evidence of their early manifestation, even before the onset of the disease. Furthermore, in association to such mood disturbance, inflammatory-dependent synaptic dysfunctions in several areas of MS/EAE brain, have been observed independently of brain lesions and demyelination. This evidence suggests that a fine interplay between the immune and nervous systems can have a huge impact on several neurological functions, including depressive symptoms, in different pathological conditions. The aim of the present review is to shed light on common traits between MDD and MS, by looking at inflammatory-dependent synaptic alterations associated with depression in both diseases.